Transnational telepathology consultations using a basic digital microscope: experience in the Italy-Slovenjia INTERREG project "Patient without borders" - Sverko Sandi; Bortolotti Nicola; Riosa Franca; Snoj Viviana; Intersimone Donatella; Beltrami Carlo A; Della Mea Vincenzo (BMC, 2011)
Abstract Background In recent years, a number of technological advancements started to modify the long standing appearance and functionalities of traditional optical microscopes used in Pathology and other medical fields. In fact, at present many new tools for microscopical visualization exist that are based on digital imaging, robotization, and remote communication. Such tools are typically adopted in activities ranging from education to telediagnosis to remote consultation. Present paper describes the features of a basic digital microscope that has been tested to verify its performance for occasional remote consultation inside an international project between Italy and Slovenija, funded by Interreg initiative of the European Regional Development Fund. Methods The system is composed by a pair of digital microscopes (Leica DMD108, Leitz Microsystems, Wetzlar, Germany) associated to a high resolution videoconferencing systems (Tandberg 990, Lysaker, Norway). The systems are connected through the Internet. Sixty histology and cytology cases have been collaboratively diagnosed between two Pathology Institutes to verify the diagnostic performance of the system, regarding the image quality point of view as well as time needed for diagnosis. The system has also been tested for compatibility with standard videoconferencing software. Results No discrepancies between local and remote diagnoses have been identified, with diagnosis time reasonably close to typical microscope observation times. Time needed for most operations is not far from that needed on a traditional microscope, except for startup. Conclusions The system can be considered usable as a standard microscope, and also for occasional remote consultations.